Analisi di movimenti oculari nella risoluzione di problemi commerciali Il ruolo delle abilità numeriche e dell'impulsività cognitiva - Dorigoni, Alessia (FrancoAngeli, 2022)
Many daily purchase decisions, such as choosing the best deal, require the integration of various kinds of information. In most commercial scenarios the consumer has to manage and compare numerical information. The present study is driven by an important research question: "in a commercial scenario with a high numerical component, is numerical ability (e.g. numeracy) the only factor that influences the accuracy of decisions?". The aim of the present paper is to understand if cognitive reflection drives the problem-solving process in these contexts. We examined attentional aspects by measuring eye movements using an SR Research Eye Link 1000 eye tracking device belonging to The Consumer Neuroscience Laboratory (ncLab) located at The University of Trento.